Case-control study of prolactin and placental lactogen in SGA pregnancies - Sharon R Ladyman; Caroline M Larsen; Rennae S Taylor; David R Grattan; Lesley M E McCowan (Bioscientifica, 2021)
Prolactin and placental lactogens increase during pregnancy and are involved with many aspects of maternal metabolic adaptation to pregnancy, likely to impact on fetal growth. The aim of this study was to determine whether maternal plasma prolactin or placental lactogen concentrations at 20 weeks of gestation were associated with later birth of small-for-gestational-age babies (SGA). In a nested case-control study, prolactin and placental lactogen in plasma samples obtained at 20 weeks of gestation were compared between 40 women who gave birth to SGA babies and 40 women with uncomplicated pregnancies and size appropriate-for-gestation-age (AGA) babies. Samples were collected as part of the 'screening of pregnancy endpoints' (SCOPE) prospective cohort study. SGA was defined as birthweight <10th customized birthweight centile (adjusted for maternal weight, height, ethnicity, parity, infant sex, and gestation age) in mothers who remained normotensive. No significant differences were observed in concentrations of prolactin or placental lactogen from women who gave birth to SGA babies compared with women with uncomplicated pregnancies. However, a sex-specific association was observed in SGA pregnancies, whereby lower maternal prolactin concentration at 20 weeks of gestation was observed in SGA pregnancies that were carrying a male fetus (132.0 ± 46.7 ng/mL vs 103.5 ± 38.3 ng/mL, mean ± s.d., P = 0.036 Student's t-test) compared to control pregnancies carrying a male fetus. Despite the implications of these lactogenic hormones in maternal metabolism, single measurements of either prolactin or placental lactogen at 20 weeks of gestation are unlikely to be useful biomarkers for SGA pregnancies.